Pengenalan Digital Marketing Dan Inovasi Dalam Meningkatkan - Adrianah; Asniwati; Yusra Nginang; Hj.Nurhaedah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The rapid increase in the use of digital technology has had a significant impact in the world of marketing, especially on a home industry business scale. This PKM aims to investigate the effect of introducing digital marketing and implementing innovation on increasing business income for home industry products. Through qualitative and quantitative research methods, we collect data from home industry business owners who have adopted digital marketing strategies and implemented innovations in their products. Introduction of digital marketing, including the use of social media, e-commerce platforms, and other online marketing techniques, has a positive impact on product visibility and increasing the number of customers. In addition, product innovations such as attractive designs, environmentally friendly packaging, and improving product quality also contribute significantly to increasing competitiveness and customer satisfaction. These findings provide valuable insight for home industry business owners and marketing practitioners regarding the positive potential of integrating digital marketing and product innovation. Therefore, business actors in the home industry sector are advised to adopt a holistic approach, combining smart digital marketing strategies with continuous product innovation, to achieve sustainable income increases and increase competitiveness in an increasingly changing market.